Effect of organic and inorganic nutrient sources on productivity, profitability and soil fertility in onion (Allium cepa) under Entisol - HARVENDRA SINGH; VINAY SINGH; JAGPAL SINGH (The Indian Journal of Agricultural Sciences, 2019)
Field experiment was conducted for two consecutive winter (rabi) seasons of 2014–15 and 2015–16 at Panwari village, Agra,Uttar Pradesh to find out the best combination of organic manures and inorganic fertilizers for increasing productivity, profitability and soil fertility in onion (Allium cepa L.) under Entisol. The experiment was laid out in randomized block design with eight treatments and three replications. The results revealed that the fresh weight of onion bulb, and bulb yields increased on application of 100% NPK. The yields of onion bulbs were significantly lower with the suboptimal dose of NPK fertilizers (75% RDF). An additional bulb yield of 7.25 t/ha was realized with 75% NPK+15 t/ha FYM over 75% NPK alone. Application of 75% RDF+6 t/ha vermicompost increased bulb yield by 29.4% over 75% RDF alone. Application of 75% RDF+15 t/ha FYM+20 kg/ha S and 75% NPK+6 t/ha vermicompost+20 kg/ha S increased the bulb yield by 38.5 and 43.8% over 75% RDF, respectively, indicating the superiority of vermicompost over FYM. The maximum content of protein (7%) was recorded with 75% NPK+15 t/ha FYM+20 kg/ha S, but maximum value of protein yield (481 kg/ha) was recorded with 75% NPK+6 t/ha vermicompost+20 kg/ ha S. Application of 75% NPK+20 kg/ha S also improved the yield (29.92 t/ha), quality, and uptake of nutrients by onion bulbs but proved inferior compared to vermicompost and FYM. The uptake of NPK and S was highest with 75% NPK+6 t/ha vermicompost+20 kg/ha S and lowest in control. Net returns (` 1,44,375/ha) and B:C ratio (3.20) were also highest with 75% NPK+6 t/ha vermicompost+20 kg/ha S. Use of organic manures decreased soil pH and their combined use with fertilizers built up organic carbon and available NPK and S in post-harvest soil.